ANALYSIS OF FACTORS CAUSING STRESS AMONG JUNIOR HIGH SCHOOL STUDENTS AND ITS IMPACT ON MENTAL HEALTH - Nazwa Annisa Nasution; Fitri Amanda br Stp; Rafif Ghulaman Zakya; Rama Haholongan; Ahmad Sultan Pasaribu (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
Stress among junior high school students has become an increasing concern in educational psychology as it affects both mental health and academic performance. This study aims to analyze the factors causing stress and its impact on students’ mental health based on recent literature. A systematic literature review was conducted using 10 relevant articles published between 2019 and 2024. Findings reveal that academic pressure, parenting style, bullying, social media use, and family economic conditions are the main contributors to stress. The consequences include anxiety, depression, sleep disturbances, reduced learning motivation, and social problems. Recommended interventions involve school counseling, digital literacy, stress management programs, parental involvement, and positive extracurricular activities. This study highlights the importance of holistic strategies from schools and families to support junior high school students’ mental well-being.